PAK UPAYA GURU PAK TERHADAP PENANGANAN MASALAH MENGATASI KESULITAN BELAJAR SISWA - Petrus Bobii; Kalis Stevanus; Chandra Kirana Luhur; Fianus Tandiongan (CARAKA: Jurnal Teologi Biblika dan Praktika, 2023)
Difficulty in learning is not uncommon among students. Learning difficulties faced by students at SMP Negeri 2 Tigi Barat, Central Papua, include reading delays that negatifly impact academic achievement. One of the learning difficulties students face is reading difficulties. This paper aims to describe the influence of PAK (Pendidikan Agama Katolik or Catholic Religious Education) teachers in addressing the issue of reading delays. To address this objective, the researcher employed a quantitative method using a questionnaire to determine the level of problem-solving in addressing students' learning difficulties, particularly in the seventh grade. The research results show a significant level with 52 respondents, where the critical value (r tabel) is 0.279, while R Square is 0.738, indicating a moderately significant category. Reading difficulties can be a challenge, but with the right approach, support, and persistence, many students can overcome this issue and improve their reading skills. It is important to remember that every student is a unique individual and may require different amounts of time to overcome their reading difficulties. Therefore, PAK teachers need to provide additional hours or reading lessons to address reading delays, thereby achieving the learning goals of their students. It is advisable to conduct regular reading exercises, ideally every day, to ensure consistency in reading practice. Additionally, involving parents in the student's reading learning process is equally important. They can assist by reading books, discussing stories, and providing moral support.